A step so grave - McPherson, Catriona, 1965- (McPherson, Catriona, 1965- Dandy Gilver., 2018)
Wedding bells are set to ring as Dandy Gilver, family in tow, arrives in windswept Wester Ross on Valentine's Day. They've come to celebrate Lady Lavinia's fiftieth birthday and to meet her daughter Mallory, a less-than-suitable bride-to-be for Dandy's son Donald. But soon love is the last thing on Dandy's mind when the news breaks that Lady Lavinia has been found dead, brutally murdered in the middle of her famous knot garden. Strange superstitions and folklore abound among the Gaelic-speaking locals. But Dandy suspects that the tangled boughs and branches around Applecross House hide something much more earthly at work ..